Priority Setting: A Method that Incorporates a Health Equity Lens and The Social Determinants of Health - Jaramillo Garcia, Alejandra Paula (Université d'Ottawa / University of Ottawa, 2011)
Research Question: This research adapted, tested, and evaluated a methodology to set priorities for systematic reviews topics within the Cochrane Collaboration that is sustainable and incorporates the social determinants of health and health equity into the analysis. Background: In 2008 a study was conducted to review, evaluate and compare the methods for prioritization used across the Cochrane Collaboration. Two key findings from that study were: 1) the methods were not sustainable and 2) health equity represented a gap in the process. To address these key findings, the objective of this research was to produce and test a method that is sustainable and incorporates the social determinants of health and health equity into the decision making process. As part of this research, the methods were evaluated to determine the level of success. Methodology: With assistance from experts in the field, a comparative analysis of existing priority setting methods was conducted. The Global Evidence Mapping (GEM) method was selected to be adapted to meet our research objectives. The adapted method was tested with assistance of the Cochrane Musculoskeletal Group in identifying priorities for Osteoarthritis. The results of the process and the outcomes were evaluated by applying the “Framework for Successful Priority Setting”. Results: This research found that the priority setting method developed is sustainable. Also, the methods succeeded in incorporating the social determinants of health and health equity into the analysis. A key strength of the study was the ability to incorporate the patients’ perspective in setting priorities for review topics. The lack of involvement of disadvantaged groups of the population was identified as a key limitation. Recommendations were put forward to incorporate the strengths of the study into future priority setting exercises within Cochrane and to address the limitations.
Keywords: priority setting; health equity; social determinants of health; osteoarthritis; setting priorities